(untitled) (Research, Society and Development, 2026)
This article aims to analyze recent scientific production that connects Artificial Intelligence (AI) and the Circular Economy (CE), focusing on the ethical, social, and governance dimensions. Based on a qualitative and exploratory literature review, 25 studies published between 2020 and 2025 were examined, selected through systematic searches on Google Scholar. The works were classified into four analytical dimensions — technical, social, ethical, and governance — according to the predominant approach adopted. The results reveal a strong predominance of studies with a technical and instrumental character, oriented toward process efficiency, productive innovation, and environmental indicators, while the social, ethical, and governance dimensions remain marginalized and fragmented. AI is often treated as a neutral tool to support sustainability, with limited problematization of its distributive impacts, ethical risks, algorithmic biases, and regulatory challenges. The lack of studies that consistently integrate AI, circular economy, and democratic governance points to a structural gap in the literature, indicating risks of reproducing inequalities and power asymmetries in the transition to circular models. It is concluded that advancing a circular economy supported by artificial intelligence requires interdisciplinary approaches that recognize the sociotechnical nature of these technologies, incorporating principles of socio-environmental justice, ethics, and responsible governance.